CODE-SWITCHING USED BY EFL LEARNERS IN NATURAL INTERACTION - Syafira Aganmar; Indah Tri Purwanti; Mahdum Adanan (International Journal of Educational Best Practices, 2022)
This study investigated kinds and reasons of code-switching employed by the EFL learners at one of the Universities in Riau Province, Indonesia, with a qualitative approach. The code-switching data were collected based on natural interactions that occurred naturally through phone calls. The participants of this study were the 7th semester students of the English Department at one of the universities in Riau province. The natural interactions through phone calls were audiotaped, and the audios were transcribed. Furthermore, the transcribed audio got classified and analyzed based on its types and functions. Besides, interviews were also conducted in this study to gather the reasons for the use or functions of code-switching based on the learners’ perspectives. Thenceforth, the classified data was validated by the experts of code-switching to make sure the data was ideally correct. The findings showed that learners used Inter-sentential code- switching and Intra-sentential code-switching. Dealing with the second research aims, the reasons for code-switching was used to clarify speech content, to talk about particular topics, to use repetition to clarify something, to show emphatic, to provide emphasis on something and also for lexical needs. However, the EFL learners at one of the Universities in Riau Province, Indonesia, not only used an English-Indonesian switching but also Indonesian-English switching in English- based conversation.